Over- and Under-Bidding in Tendering - Vincent van den Berg (Tinbergen Institute, 2013)
Consider a government tendering the right to operate, for example, an airport, telecommunication network, or utility. There is an 'incumbent bidder' who owns a complement or substitute facility, and one entering 'new bidder'. With a 'standard auction' on the payment to the government, the incumbent is willing to bid higher than its expected profit from the facility as winning implies that it is a monopolist instead of a duopolist. The incumbent is therefore more likely to win. However, it tends to have a lower expected surplus unless the new bidder can never win, which occurs with 'private values' when the facilities are strong complements or substitutes and always with 'common values'. The 'standard auction' leads to an unregulated outcome which hurts consumers as tendered facilities tend to have limited competition. The government could improve the outcome by endogenously regulating using a 'price auction' on the price to be asked to consumers. Now, it depends who is advantaged: with complements, the incumbent bids below its marginal cost and is more likely to win; with substitutes, it bids above and is less likely to win. The same effects occur in auctions on service quality or number of users. In many settings, the advantaged bidder always wins, and this can greatly affect the competition for the field.
Keywords: D43; D44; L51; R42; 330; tendering; overbidding; advantaged bidders; network markets